Preventive defense : a new security strategy for America - Carter, Ashton B. (Brookings Institution Press, 1999)
"William J. Perry and Ashton B. Carter draw on their experience as leaders of the U.S. Defense Department to propose a new American security strategy for the twenty-first century. After a century in which aggression had to be defeated in two world wars and then deterred through a prolonged cold war, the authors argue for a strategy centered on prevention." "The authors' preventive defense strategy concentrates on the dangers that, if mismanaged, have the potential to grow into true threats to U.S. survival in the next century." "They also argue for better management of the defense establishment so the United States will retain a strong military prepared to cope with all contingencies deter aggressors and win a conflict it deterrence faits."--Jacket.